Transformation of Community Reading Garden Based on Social Inclusion - Dinantika, Nazla Dara (International Journal of Cultural and Social Science, 2024)
Taman Bacaan Masyarakat (TBM) is one of the means of providing reading materials managed by the community and the community. The purpose of this research is to find out the changes in TBMs in the context of implementing social inclusion in North Sumatra. Using a qualitative approach, case studies were conducted on several TBMs in North Sumatra that successfully implemented changes towards social inclusion. Information was collected through observation, in-depth interviews and document studies. The results showed that TBMs have transformed from just a provider of reading materials into inclusive literacy for all levels of society, regardless of social, economic, cultural backgrounds, or special abilities. This change can be seen in the programs implemented such as mobile libraries, literacy courses for people with disabilities, and reading and learning activities together for marginalized communities. Factors that support the success of change are management commitment, active community participation and partnerships with various parties. This study concludes that TBMs play an important role in promoting social inclusion by providing equal access to literacy to all levels of society.